(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical symptoms of isolated periarthritis of the shoulder according to modern medicine and traditional medicine. Research objects and methods: A cross-sectional descriptive study was conducted on 60 patients diagnosed with isolated periarthritis of the shoulder. Results: The average age was 60.03 ± 11.18 years, with a higher proportion of females than males (2.16/1). The average VAS score was 5.20 ± 1.31 points, with 100% of patients experiencing restricted shoulder joint mobility. Ultrasound imaging revealed inflammation of the supraspinatus tendon in 68.3% of cases and the subacromial bursa in 51.7%. According to the traditional medicine, 98.3% of patients belong to interior syndrome group, 95% of patients belong to asthenia with sthenia. The prevalence of cold syndrome was higher than heat syndrome, with wind-cold-damp paralysis syndrome take the most percentage at 38.3%. Conclusion: This study significantly guides diagnosis, treatment, and disease assessment by integrating traditional and modern medicine approaches.